Model Latihan Keterampilan Dibbling Sepak Bola Berbasis Koordinasi Untuk Atlet Sma Kota Mataram - Soemardiawan Soemardiawan; Susi Yundarwati (Jurnal Ilmiah Mandala Education (JIME), 2020)
The purpose of this research and development is to produce a coordination-based soccer team on soccer for high school students in the city of Mataram. In addition, this research and development is carried out to obtain in-depth information about the development and application of soccer dribbling models, to determine the effectiveness, efficiency and attractiveness of children to the models created. This study uses the Research & Development (R & D) development research method from Borg and Gall. The subjects in this research and development were high school students consisting of 60 children. The instruments used in this research and development were questionnaires, questionnaires, as well as a soccer dribbling test instrument which was used to collect data on soccer for high school aged children, while the stages in this research and development were: (1) needs analysis, (2) expert evaluation (initial product evaluation); (3) limited trials (small group trials); and (4) main testing (field testing). The model effectiveness test uses soccer dribbling skills to determine the skill level of dribbling football for high school age before giving treatments in the form of a coordination-based soccer training model developed and to determine the level of dribbling skills after treatment or treatment from the initial tests carried out, the dribbling level is obtained. students were 750, then after being given treatment in the form of a dribbling model, the final test student dribbling skill level was obtained at 940. Then this ball dribbling model is effective in improving learning to dribble soccer for high school age. Based on the data obtained, from the results of field trials and discussion of the results of the study it can be concluded that: with the coordination-based training model for training skills in coordination-based football bling for Mataram city high school athletes, it is effective and efficient, innovative can improve dribbling practice and apply dribbling properly, evidence is obtained. This increase is shown in the results of testing the pretest and posttest results, there is a significant difference between before and after the treatment model.